Segmentasi Huruf Hijaiyah Menggunakan Metode Connected Component Labeling - Putri, Audini Nifira; Suputra, I Putu Gede Hendra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2020)
Arabic letters or Hijaiyah letters recognition is a challenge in itself because one letter consists of more than one character, namely the main character, companion character such as dots and lines, and punctuation called harakat. The image segmentation process is the most important in a character recognition system because it affects the separation of objects in an image. In this research, Hijaiyah letter segmentation aims to separate the letters according to the character of each letter using the Connected Component Labeling (CCL) method. Merging labels on each character will be done by looking for the Euclidean distance value from adjacent centroids. The experiment succeeded in segmenting each Hijaiyah character with an accuracy value of 86%.